Micromachined multimode interference device in flat-fiber - Ambran, S.; Holmes, C.; Gates, J.C.; Webb, A.S.; Adikan, Faisal Rafiq Mahamd; Smith, P.G.R.; Sahu, J.K. (2010)
We demonstrate a new approach for fabricating multimode interference (MMI) devices using micromachining of a novel flat-fiber platform. A 1x3 splitter has been demonstrated together with spatial output mode control by index tuning of material within micromachined trenches.